Diagnosis of spinal muscular atrophy in an SMN non-deletion patient using a quantitative PCR screen and mutation analysis. Issue 8 (August 1998) - Parsons, D W; McAndrew, P E; Allinson, P S; Parker, W D; Burghes, A H; Prior, T W
Abstract : We report a child with clinical findings consistent with Werdnig-Hoffmann disease (spinal muscular atrophy type I) who was found not to have the homozygous absence of the survival motor neurone (SMN(T)) gene observed in approximately 95% of spinal muscular atrophy patients. A quantitative PCR based dosage assay for SMN(T) copy number showed that this patient possessed a single copy of the SMN(T) gene. Heteroduplex and sequence analysis of the remaining copy of SMN(T) showed a 2 base pair deletion within exon 4 which produces a frameshift and premature termination of the deduced SMN(T) protein. This protocol of initial SMN(T) gene dosage analysis followed by mutation detection allows identification of SMA compound heterozygotes (patients lacking one copy of SMN(T) and having another mutation in their other copy), thereby increasing the sensitivity of SMA molecular diagnosis.